Tiny, Tiny Copyright: An Examination of the Copyrightability of Sampler Instruments and Its Impact on Derivative Works - King, Jeremy (The Columbia Journal of Law & the Arts, 2021)
Sound recordings of musical compositions used to be simple. Sounds would be created by voices and acoustic instruments. Those sounds would then be captured by microphones and fixed on analog tape. What the listener heard was simply an immortalized version of what happened in the room. With the advent of digital recording technology, this has been forever changed in ways that offer infinite possibilities—and infinite new challenges. These days, sounds are typically recorded in a digital format, which allows them to interface with computer software in myriad ways. Most consumers only interact with these files—in the form of MP3, WAV, M4A, and AAC files, or other digital formats used by download or streaming services—to listen to and distribute music. However, these files can be used in much more specialized ways, such as for playback on a digital instrument. This type of use and its copyright implications are the focus of this Note. Digital instruments such as keyboards and drum pads allow the user to use digitally recorded material in a new musical context. The digital instrument (known as a “controller”) serves as a group of “play buttons” for prerecorded or synthesized material. The user is able to strike or press these buttons in the same way they would strike a drum or press a keyboard key. This mechanism allows someone proficient in drums or piano to play a digital instrument using essentially the same technique used on its acoustic counterpart, but with an almost infinite array of potential sounds emanating as a result. This technology can be used to create a digital drum set that can be programmed to sound like twenty different, customizable drum sets or to create a keyboard that can switch between sounding like a Steinway grand piano and a Hammond B-3 organ. The artist can reproduce the sounds of different drum sets or keyboard instruments, reproduce the sounds of various other instruments, or even reproduce multiple instruments at once. Sometimes the tones triggered by a digital controller are what is referred to as a “soft synth”—a software tone generator that creates (“synthesizes”) the sounds produced in real time. However, the same technology may also be used as a “sampler instrument,” which serves as the “play button” for a short sound recording. Sampler instruments are most commonly created by taking the instrument that is being imitated into a recording studio and making individual recordings of each note that are playable on the instrument at multiple volumes (referred to as “velocity levels”). This process captures the nuanced differences in tone color between, for example, a quiet trumpet and a blaring trumpet. These recordings are referred to as “samples.” A complete set of samples that collectively imitate an acoustic instrument constitutes a “sampler instrument,” and a collection of multiple sampler instruments constitutes a “sample library.” When the player of a sampler instrument strikes the key or drum pad (the “trigger”), the velocity with which it is struck is communicated to a computer via Musical Instrument Digital Interface (“MIDI”) to select which recording is played back, simulating the sound that would have been produced if an actual trumpet player had played the notes with the same intention. As the use of sampler instruments became the new normal (especially for keyboard players), a cottage industry sprang up around the customization and design (or “programming”) of these instruments in order to take advantage of the sonic possibilities afforded by the technology. This customization may be accomplished by deciding which keys will play certain samples, by programming certain keys to play multiple samples at once and balancing the samples’ volumes to create a new texture, by adjusting the pitch at which a sample will play, or even by using many other design elements to create a brand new software instrument, custom built for the performance of a specific musical composition. Creators in these fields face challenges in safeguarding the market value of their work to which copyright law is uniquely suited. First, despite the technological lengths to which the creators of sample libraries go to prevent unauthorized use, there will always be workarounds allowing those motivated enough to skirt the Terms of Service contracts, so legal recourse of some sort is a necessary backstop. Second, due to the ease with which digital files can be copied, contract law alone is insufficient to stop unauthorized use by third parties who were never in privity of contract with the sample library’s owner. Additionally, for custom programming, there are fewer technological means employed to prevent unauthorized use. This programming is typically rented rather than sold, creating a high likelihood of a licensee retaining a copy of the rented file after the term of the license, only to share it with a third party, thereby depriving the programmer of further licensing revenue. Because the work is typically visible to the user or easily reverse-engineered, trade secret protection is not available. Therefore, in the most likely scenario, where a valid licensee rents programming only to then create and distribute a copy to another potential licensee, copyright law would afford the owner a cause of action against the potential licensee that contract law and trade secret law would not. The popularization of this technology raises several copyright issues that have not yet been addressed by the courts. First, are the samples themselves copyrightable? In Part I, I apply the requirements under the Copyright Act and conclude that potential arguments against copyright protection for samples do not apply. In Part II, I argue that custom programming—the creation of customized programming that entails the selection and arrangement of individual samples—should itself be eligible for copyright protection as a compilation. Finally, in Part III, I ask whether custom programming or the use of samples in recordings could constitute copyright infringement, concluding that such uses are likely to be found to be de minimis or fair use.